Sedentary Conditions Promote Subregionally Specific Changes in Brain-Derived Neurotrophic Factor in the Rostral Ventrolateral Medulla - Fyk-Kolodziej, Bozena E.; Mueller, Patrick J. (Frontiers in Physiology, 2021)
A sedentary lifestyle is the top preventable cause of death and accounts for substantial socioeconomic costs to society. The rostral ventrolateral medulla regulates blood pressure under normal and pathophysiological states, and demonstrates inactivity-related structural and functional neuroplasticity, which is subregionally-specific. The purpose of this study was to examine pro- and mature forms of brain-derived neurotrophic factor and their respective receptors in the male rat RVLM and its rostral extension following sedentary versus active (running wheels) conditions (10-12 weeks). We used subregionally-specific Western blotting to determine that the mature form of brain-derived neurotrophic factor and its ratio to its pro-form were lower in more caudal subregions of the rostral ventrolateral medulla of sedentary rats but higher in the rostral extension when both were compared to active rats. The full-length form of the tropomyosin receptor kinase B receptor and the non-glycosylated form of the 75 kilodalton neurotrophin receptor were lower in sedentary compared to active rats. The rostrocaudal patterns of expression of the mature form of brain-derived neurotrophic factor and the full-length form of the tropomyosin receptor kinase B receptor were remarkably similar to the subregionally-specific patterns of enhanced dendritic branching, neuronal activity and glutamate-mediated increases in sympathetic nerve activity observed in previous studies performed in sedentary rats. Our studies suggest signaling pathways related to brain-derived neurotrophic factor within subregions of both the rostral ventrolateral medulla and its rostral extension contribute to cardiovascular disease and premature death related to a sedentary lifestyle.